2009
DOI: 10.1089/ars.2008.2270
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy by Reactive Oxygen Species (ROS): Implications for Cancer Progression and Treatment

Abstract: Reactive oxygen species (ROS) have been identified as signaling molecules in various pathways regulating both cell survival and cell death. Autophagy, a self-digestion process that degrades intracellular structures in response to stress, such as nutrient starvation, is also involved in both cell survival and cell death. Alterations in both ROS and autophagy regulation contribute to cancer initiation and progression, and both are targets for developing therapies to induce cell death selectively in cancer cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
505
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 678 publications
(533 citation statements)
references
References 114 publications
23
505
0
5
Order By: Relevance
“…Therefore, inhibition of prosurvival members of the Bcl-2 family by BH3 mimetics, especially by pan-Bcl-2 inhibitors, might also hamper the antioxidative capacity of cells. Given the fact that oxidative stress is also known to stimulate autophagy in several experimental paradigms (53,54), it is presumably involved in the prominent induction of gossypol-dependent autophagy observed in our experiments. Indeed, (−)-gossypol was previously shown to be a potent inductor of oxidative stress in colorectal cancer cells (22).…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, inhibition of prosurvival members of the Bcl-2 family by BH3 mimetics, especially by pan-Bcl-2 inhibitors, might also hamper the antioxidative capacity of cells. Given the fact that oxidative stress is also known to stimulate autophagy in several experimental paradigms (53,54), it is presumably involved in the prominent induction of gossypol-dependent autophagy observed in our experiments. Indeed, (−)-gossypol was previously shown to be a potent inductor of oxidative stress in colorectal cancer cells (22).…”
Section: Discussionmentioning
confidence: 73%
“…More importantly, the inhibition of autophagy markedly enhanced the ROS level in 3,4,4'-THS-treated A549 cells. Autophagy can reportedly remove damaged mitochondria to limit ROS amplification [30] . The mitochondria pathway is a key signaling pathway in apoptosis induction (the intrinsic cell death pathway).…”
Section: Discussionmentioning
confidence: 99%
“…In autophagy parts of the cytoplasm is sequestered into a double-membrane autophagosome and delivered to lysosomes for breakdown and recycling [31]. Azab et al (2009) revealed that 2ME2 induces autophagy in human glioblastoma-astrocytoma epithelial-like cell line (U87), human cervical adenocarcinoma cells (HeLa) and transformed human embryonic kidney cells (HEK293) [32].…”
Section: Discussionmentioning
confidence: 99%